Psychology in Education / Second Edition - Hughes Malcolm; Walkup Vivienne; Woolfolk Anita (Pearson, 2013)
Essential reading for anyone studying or interested in education and learning from a psychology perspective. Preface, Acknowledgements, Teachers and Teaching and Educational Psychology, Learners, Cognitive Development and Language, Personal and Social and Emotional Development, Learner Differences and Learning Needs, Culture and Diversity, Learning and Motivation, Behavioral Views of Learning, Cognitive Views of Learning, Complex Cognitive Processes, Social Cognitive and Constructivist Views of Learning, Motivation in Learning and Teaching, Engaged Learning: Cooperation and Community, Teaching and Assessing, Creating Learning Environments, Teaching for Learning, Standardized Testing, Classroom Assessment, Glossary, References, Index.